Tindakan Penyalahgunaan Nikah Siri Menurut Ketentuan Hukum Pidana - Yunia Lestari (Bhirawa Law Journal, 2022)
As widespread as siri’s marital trend has been, it is not only the easy process,lowbudget, and parental factors. Siri’s marriage was merely a matter of religious law,without regard to Indonesia’s criminal laws that should continue to be enforced. Morecomplex reasons for many of siri’s marital events should be avoided because theyviolate criminal law. But it is popular until it becomes fashionable today. Still the prosand konra of such cases. However, the counter to women at the time of death is siribecause most perpetrators are married men. Since the husband was secretly marriedwithout the wife’s knowledge and would also later become an issue of the legitimacyof siri’s child. Siri’s many marital woes are due to the excessive lusts of the man whotrifling legal affairs in spite of future risks.